Inflammation enhances the vaccination potential of CD40‐activated B cells in mice. Issue 2 (27th December 2016) - Mathieu, Mélissa; Odagiu, Livia; Gaudot, Léa; Daudelin, Jean‐François; Melichar, Heather J.; Lapointe, Réjean; Labrecque, Nathalie
Abstract : Vaccination with CD40‐activated B cells produces a functional CD8+ T‐cell effector response. However, in comparison to BMDC vaccination, the reduced quality and duration of the T‐B‐cell interaction results in decreased provision of signal 1–3 and precludes memory generation. Increasing inflammation allows for memory CD8+ T‐cell differentiation. Abstract : Vaccination with antigen‐pulsed CD40‐activated B (CD40‐B) cells can efficiently lead to the in vivo differentiation of naive CD8 + T cells into fully functional effectors. In contrast to bone marrow‐derived dendritic cell (BMDC) vaccination, CD40‐B cell priming does not allow for memory CD8 + T‐cell generation but the reason for this deficiency is unknown. Here, we show that compared to BMDCs, murine CD40‐B cells induce lower expression of several genes regulated by T‐cell receptor signaling, costimulation, and inflammation (signals 1–3) in mouse T cells. The reduced provision of signals 1 and 2 by CD40‐B cells can be explained by a reduction in the quality and duration of the interactions with naive CD8 + T cells as compared to BMDCs. Furthermore, CD40‐B cells produce less inflammatory mediators, such as IL‐12 and type I interferon, and increasing inflammation by coadministration of polyriboinosinic‐polyribocytidylic acid with CD40‐B‐cell immunization allowed for the generation of long‐lived and functional CD8 + memory T cells. In conclusion, it is possible to manipulate CD40‐B‐cell vaccination to promote the formation of long‐lived functional CD8 + memory T cells, a key step before translating the use of CD40‐B cells for therapeutic vaccination.